Experimental reasons for the variable efficiencies of organic electrocatalysts used for converting carbon dioxide to methanol - Budanovic, Maja (2022)
Pyridinium (the protonated form of pyridine) and related compounds have been proposed to be promising homogenous electrocatalysts in the electrochemical reduction of CO2 to methanol due to the low overpotential required to achieve faradaic yields of about 20 %, although the percentage yields vary dramatically between different research groups. In this study, experimental conditions were varied during the electrolysis of CO2 at a platinum electrode in the presence of pyridinium to determine the reasons for the discrepancies in the yields of methanol reported between different research groups. Two other vitamin-based and environmentally friendly nitrogen-containing heterocyclic compounds (nicotinamide and nicotinic acid) which have structural similarities to the promising but toxic pyridine homogeneous electrocatalyst, were also investigated as alternative electrocatalysts for the reduction of CO2 in aqueous acidic media. Cyclic voltammetry studies suggest that nicotinamide and nicotinic acid (forms of vitamin B3) follow a similar reaction mechanism as pyridine in the reduction of CO2. Relatively low faradaic yields of methanol were obtained during controlled potential electrolysis experiments for all the electrocatalysts (0.4–1.9 %) which can be attributed to the low solubility of CO2 along with the competing hydrogen evolution reaction. It was found that adventitious sources of methanol were responsible for greatly inflating the apparent yields of methanol unless scrupulous care was taken in controlling the experimental conditions. The problem with background methanol is particularly difficult to control due to the electrochemical reactions typically generating products in the parts per million range, considerably lower than normal synthetic reactions.